Impact of Authentic Leadership Practices of Principals on Employees’ Organizational Trust and Work Engagement (Journal of Asian Development Studies, 2025)
This study explored the impact of authentic leadership practices of principals on employees' organisational trust and work engagement. There has been limited research on these dynamics in educational settings compared to business contexts. The research was conducted using a correlational approach. The study's population comprised all teachers working in public high and higher secondary schools of the Gujrat Division. A sample of 345 teachers was selected using the purposive sampling method, based on the Krejcie and Morgan (1970) population and sample size table. The researcher developed an instrument in the form of a five-point Likert scale questionnaire. The researcher surveyed 345 teachers using the questionnaire to examine the correlation among authentic leadership, organisational trust, and work engagement. Expert opinions were obtained to ensure validity, and a pilot test was conducted to confirm the reliability of the research tool, achieving an overall Cronbach's Alpha of 0.87. All data were collected by the researcher and analysed using SPSS version 26. The study found significant positive relationships among the variables. authentic leadership was moderately correlated with organisational trust (r = 0.787) and work engagement (r = 0.773), while organisational trust was strongly correlated with work engagement (r = 0.779). Regression analyses showed that authentic leadership explained 62% of organisational trust and, together with organisational trust, explained 69% of the variance in work engagement, indicating highly significant effects. This research recommends that school leaders be provided with professional development in self-awareness, transparency, ethical judgment, and balanced thinking to build trust and enhance teachers' work engagement and commitment.